2020
DOI: 10.1039/c9en00938h
|View full text |Cite
|
Sign up to set email alerts
|

The rise of the nanomaterial metabolite corona, and emergence of the complete corona

Abstract: Metabolites present in the corona may play a key role in biological recognition of nanomaterials yet remain a much-overlooked aspect of the corona.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 149 publications
(208 reference statements)
0
58
0
Order By: Relevance
“…Whilst in theory, an analogous framework is expected to exist in the environmental corona, with greater heterogeneity in the structure and components, a wider range of molecules of different molecular weights and compositions are competing for the surface of the ENM. [24,43] To date, the structure-activity relationships in environmental corona formation on ENMs is not well understood, as it is dependent on the physicochemical properties of ENMs and chemical reactivities of eco-molecules.…”
Section: Environmental Corona Formation On Enms In Aquatic Environmenmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst in theory, an analogous framework is expected to exist in the environmental corona, with greater heterogeneity in the structure and components, a wider range of molecules of different molecular weights and compositions are competing for the surface of the ENM. [24,43] To date, the structure-activity relationships in environmental corona formation on ENMs is not well understood, as it is dependent on the physicochemical properties of ENMs and chemical reactivities of eco-molecules.…”
Section: Environmental Corona Formation On Enms In Aquatic Environmenmentioning
confidence: 99%
“…Recently, it has also been suggested that metabolites may be an important co-constituent alongside proteins. [24] Secreted proteins are particularly important for microorganisms in water systems, which have a wide range of biological functions from self-protection to reproduction. [91,92] For example, cytochrome c (OmcA) is secreted by Shewanella oneidensis MR-1 (S. oneidensis MR-1), belonging to a bacterial extracellular protein.…”
Section: (6 Of 23)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a limited number of studies have investigated a broader range of metabolites and demonstrated that a wide array of metabolites can interact with NMs to form a metabolite corona. [ 26–29 ] Yet, the concept of a small molecule corona, or indeed the realization that the presence of metabolites within the protein corona may mediate the NM behavior, has been largely overlooked in nanosafety to date. Here, characterization of the selective adsorption of small molecules to NMs, forming a metabolite corona, and the impact of proteins on the composition of the small molecule corona are presented.…”
Section: Introductionmentioning
confidence: 99%
“…The biological and environmental relevance of nanomaterial coronas is a central issue to advance nanobiosciences, nano(eco)toxicology, and nanosafety research in a broad sense [ 73 , 74 , 75 ]. In this regard, Nasser and Lynch (2016) [ 76 ] showed that protein eco-corona formation should be considered during toxicity assessment of nanomaterials with the D. magna model.…”
Section: Resultsmentioning
confidence: 99%